Sundanese Culture Through Digital Literacy: Efforts to Raise Public Awareness of Local Cultural Heritage - Muhamad Daud Yusuf (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This research examines the role of digital literacy in preserving Sundanese culture and raising public awareness about local cultural heritage. Sundanese culture, as one of the largest cultural heritages in Indonesia, faces serious challenges in maintaining its existence, especially among the younger generation. The research method used is a literature review, including analysis of literature related to Sundanese culture, cultural preservation methods, and digital literacy. The results show that digital literacy has significant potential in preserving Sundanese culture through the use of social media platforms to creatively promote culture. Identified challenges include limited internet access and lack of public understanding. Proposed strategies include improving internet infrastructure, digital literacy education, and developing engaging content. In conclusion, digital literacy plays an important role in increasing public knowledge and participation in preserving Sundanese culture, while maintaining a balance between modernization and traditional values